Enhance Photothermal Stability of Hybrid Perovskite Materials by Inhibiting Intrinsic Ion Migration. Issue 9 (21st July 2022) - Liu, Dachang; Zhao, Qiangqiang; Li, Zhipeng; Sun, Xiuhong; Zhang, Bingqian; Shao, Zhipeng; Chen, Chen; Hao, Lianzheng; Wang, Xianzhao; Gao, Caiyun; Li, Yimeng; Wang, Xiao; et al.
Abstract : The degradation of the perovskite solar cells (PSCs) is closely related to phase decomposition, phase separation, and structural collapse, which mainly originates from the intrinsic ion migration under light soaking and thermal stress. Herein, the composition of perovskite materials is regulated based on its ion migration characteristics. By systematically studying the effect of A‐site cations on the ion migration and photothermal stability of organic–inorganic hybrid perovskite materials, it is found that the codoping of appropriate methylammonium (MA) and Cs cation in the formamidinium (FA)‐rich perovskite is favorable for the highly efficient and stable PSCs. The optimized triple‐cation FA0.90 Cs0.04 MA0.06 PbI3 exhibits significantly improved photothermal stability in comparison with the double‐cation and Br‐containing perovskite materials. Moreover, the optimized triple‐cation device demonstrates excellent operation stability at maximum power tracking, and maintains 87% of initial efficiency after 1800 h. Abstract : The composition of perovskite materials is regulated based on its ion migration characteristics. It is found that the codoping of appropriate methylammonium and Cs cation in the formamidinium‐rich perovskite is favorable for highly efficient and stable perovskite solar cells. The optimized triple‐cation FA0.90 Cs0.04 MA0.06 PbI3 devices maintain 87% of the initial efficiency after operating for 1800 h.